2007
DOI: 10.1080/02640410600818416
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of static stretching on characteristics of the isokinetic angle – torque relationship, surface electromyography, and mechanomyography

Abstract: The aims of this study were to examine the acute effects of static stretching on peak torque, work, the joint angle at peak torque, acceleration time, isokinetic range of motion, mechanomyographic amplitude, and electromyographic amplitude of the rectus femoris during maximal concentric isokinetic leg extensions at 1.04 and 5.23 rad x s(-1) in men and women. Ten women (mean +/- s: age 23.0 +/- 2.9 years, stature 1.61 +/- 0.12 m, mass 63.3 +/- 9.9 kg) and eight men (age 21.4 +/- 3.0 years, stature 1.83 +/- 0.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 65 publications
(207 reference statements)
3
82
1
7
Order By: Relevance
“…is inversely proportional to the stiffness of an active muscle. 4 Evetovich et al 20 reported stretching-induced increases in MMG amplitude for the biceps brachii muscle; however, other studies 11,15,32 have shown no changes in MMG amplitude after stretching. Surface EMG amplitude may provide insight regarding motor unit activation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…is inversely proportional to the stiffness of an active muscle. 4 Evetovich et al 20 reported stretching-induced increases in MMG amplitude for the biceps brachii muscle; however, other studies 11,15,32 have shown no changes in MMG amplitude after stretching. Surface EMG amplitude may provide insight regarding motor unit activation.…”
mentioning
confidence: 98%
“…11 Because previous studies 9,34 used the isokinetic angletorque relationship as a global indicator of the length-tension relationship, variables such as peak torque (PT), the joint angle at PT (APT), and the timeaveraged area under the curve (mean power output [MP]) of the isokinetic angle-torque curve may provide insight regarding the effects of static stretching on the length-tension relationship during eccentric muscle actions. However, the relationship between stretching-induced changes in muscle strength and the length-tension relationship is speculative and requires further exploration.…”
mentioning
confidence: 99%
“…Esses achados corroboram com os do presente estudo, no qual a intensidade da atividade neuromuscular dos ísquios-tibiais durante uma atividade predominantemente excêntrica não foi alterada. No entanto, a maioria dos estudos 1,20,22 que avaliaram o efeito imediato do alongamento na amplitude eletromiográfica, realizaram uma contração concêntrica ou isométrica e observaram uma diminuição na ativação muscular.…”
Section: Discussionunclassified
“…Evidências recentes sugeriram que o alongamento pré-exercício pode comprometer a habilidade muscular para produção de força má-xima 5,7,8,[21][22][23] . De acordo com Cramer et al 1 , a indução da diminuição de força pelo alongamento pode ser explicada através de alterações nos fatores neuromusculares como diminuição na ativação da unidade motora e/ou mudanças da sensibilidade reflexa.…”
Section: Introductionunclassified
“…Nesse sentido, postula-se que o aumento do comprimento de repouso do sarcômero, devido a rotinas de alongamento estático, exigiria que o músculo trabalhasse em uma maior amplitude de movimento para atingir os mesmos níveis de tensão máxima alcançados sem a rotina de alongamentos, mudando a região onde o maior número de pontes cruzadas seria formado e, consequentemente, a maior capacidade de produzir força (Cramer et al, 2007;Fowles et al, 2000;Herda, Cramer, Ryan, McHugh, & Stout, 2008 No presente estudo, não foi observada queda significativa no desempenho do teste de 10-RM em nenhuma das angulações testadas (90° e amplitude total). Deve-se frisar que o presente estudo utilizou um volume menor de alongamentos estáticos (02 x 30 s) para os músculos testados, o que pode explicar esse fato.…”
Section: Análise Estatísticaunclassified